Towards formal analysis of wireless LAN security with MIS protocol. (14th March 2011) - You, Ilsun; Hori, Yoshiaki; Sakurai, Kouichi
In 2004, the MIS and MISAUTH protocols (shortly MISP) were proposed for secure and fast connection in Wireless LAN (WLAN). Since then, several studies were conducted to evaluate MISP. However, because of the lack of formal security analysis, the security measures provided by them cannot be trusted to be precise and reasonable. Motivated by this, we formally analyse MISP based on both BAN-logic and the Automated Validation of Internet Security Protocols and Applications (AVISPAS) tool. This analysis clearly shows that MISP suffers from weak Session Key (SK) while being vulnerable to Denial of Service (DoS) attack. We discuss these weaknesses and related attacks in detail, and also provide considerable comments for implementation of MISP.